2015
DOI: 10.1002/cam4.428
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative neutrophil:lymphocyte ratio and postoperative NSAID use as predictors of survival after lung cancer surgery: a retrospective study

Abstract: The association between neutrophil:lymphocyte ratio (NLR) and poor long-term outcomes in patients with non–small-cell lung cancer (NSCLC) has been demonstrated in numerous studies. The benefit of perioperative administration of anti-inflammatory drugs on these outcomes has not been well established. Our aim in this retrospective study was to investigate the effects of postoperative nonsteroidal anti-inflammatory drug (NSAID) administration and NLR on tumor recurrence and survival in patients' undergoing surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 22 publications
2
58
1
3
Order By: Relevance
“…The characteristics of the 18 studies are summarized in Table I. A total of 7 studies were conducted in Western countries, including the UK (17,26,34), USA (28), Spain (20) and Italy (22,34), 1 study was performed in Turkey (23), and 10 studies were performed in East Asian countries, including Japan (18,19,31,32), Korea (21,25) and China (24,27,30,33). The study published by Mitchell et al (29) included patient data from 33 countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the 18 studies are summarized in Table I. A total of 7 studies were conducted in Western countries, including the UK (17,26,34), USA (28), Spain (20) and Italy (22,34), 1 study was performed in Turkey (23), and 10 studies were performed in East Asian countries, including Japan (18,19,31,32), Korea (21,25) and China (24,27,30,33). The study published by Mitchell et al (29) included patient data from 33 countries.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies evaluated 16 populations of patients with NSCLC (17-24,26-29,31-34) and 2 populations of patients with SCLC (25,30). The 2 studies on SCLC reported tumor staging information as limited and extensive disease, so only the staging information from the studies regarding NSCLC were considered Only 1 study by Sarraf et al (17) evaluated all tumor stages, 8 studies evaluated early-stage tumors (23,(26)(27)(28)(29)(31)(32)(33), and 6 studies evaluated late-stage tumors (18,(20)(21)(22)24,34). The study by Tomita et al (19) evaluated stages IA/III/IV.…”
Section: Resultsmentioning
confidence: 99%
“…Some clinically available inflammatory biomarkers have been identified to improve and guide therapy in patients with cancer, particularly those with NSCLC. 5 We previously reported the importance of the preoperative neutrophil-to-lymphocyte ratio in the context of NSCLC, indicating that those with a high preoperative inflammatory status have an elevated mortality risk; however, other investigated markers, including the platelet-to-lymphocyte ratio, have been shown to correlate with poor prognosis in various types of cancer. [6][7][8][9] The interaction between platelets and cancer cells, as well as between platelets and immune cells, has previously been described, and platelets may mediate tumor growth by stimulating angiogenesis and inducing immunosuppression through the release of growth factors.…”
Section: Introductionmentioning
confidence: 98%
“…5 Similarly, use of nonsteroidal antiinflammatory drugs (NSAIDs) has been implicated in the modulation of cancer-related inflammation; moreover, use of NSAIDs could reduce proliferation, invasion, and micrometastasis of malignant cells by reducing the inflammatory state associated with the tumor microenvironment and by promoting apoptosis in cancer cells. [14][15][16] In the context of oncological surgery, a retrospective study demonstrated an association between intraoperative use of NSAIDs and improved oncological outcomes in breast cancer; this finding may be the result of a reduction in the inflammatory response associated with surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation